THE INFLUENCE OF TIME MANAGEMENT ON WORK-LIFE BALANCE IN ENTREPRENEURSHIP STUDENTS - Vania Aisya Putri; Laila Listiana Ulya (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study aims to examine the effect of time management on work-life balance among student entrepreneurs. The research employed a quantitative method with a purposive sampling technique involving student entrepreneurs at Universitas Negeri Semarang who had been running their businesses for at least three months. Data were collected using the Time Management and Work-Life Balance instruments, both of which had undergone validity and reliability testing. Hypothesis testing was conducted using linear regression analysis with a bootstrapping technique in IBM SPSS Statistics version 23. The results indicate that time management has a positive and significant effect on work-life balance. The ability to set priorities, organize schedules, and manage activities effectively plays an important role in helping student entrepreneurs balance academic demands, business activities, and personal life.